Reduction of Bacteria in Relation to Feeding Regimes When Treating Aquaculture Waste in Fly Larvae Composting - Lopes, Ivã Guidini [UNESP]; Lalander, Cecilia; Vidotti, Rose Meire [UNESP]; Vinnerås, Björn (Frontiers, 2020)
This study evaluated the impact of feeding regimes on process performance and inactivation of microorganisms during treatment of aquaculture waste with black soldier fly (BSF) larvae. In three treatments (T1–T3), a blend of reclaimed bread and aquaculture waste was used as substrate for BSF larvae. In T1, the substrate was inoculated with four subtypes of Salmonella spp. and Escherichia coli (both at 1% w/w), and offered only once, at the beginning of the 14-day trial. In T2 and T3, the substrate was supplied on three different days, with contaminated substrate provided only the first event in T2 and in all three events in T3. Provision of a lump sum feeding (T1) proved unfavorable for larval growth and process efficiency, but did not affect the microbial reduction effect. The total reduction in Salmonella spp. was approximately 6 log10 in T1 and T2, and 3.3 log10 in T3, while the total reduction in E. coli was approximately 4 log10 in T1 and T2, and 1.9 log10 in T3. After removing the larvae, the treatment residues were re-inoculated with Salmonella spp. and E. coli. It was found that the inactivation in both organisms continued in all treatments that originally contained BSF larvae (T1–T3), suggesting that antimicrobial substances may have been secreted by BSF larvae or by its associated microbiota.
Keywords: BSF; ecotechnology; Escherichia coli; hygienization; S. Dublin; S. Typhi; S. Typhimurium; Salmonella Senftenberg